Recent Advances in Mesoporous Materials and Their Biomedical Applications - Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón (IOAP-MDPI, 2022)
Since the beginning of civilization, porous materials have been used for medical purposes. Some studies have reported that the first uses of applications of porous materials were carried out by the Ancient Egyptian or Western Africans, where porous charcoal or clay minerals were used as antidiarrheal medicine [1,2]. The use of charcoal continued to be used for medical purposes throughout history. Indeed, the Hindi civilization used charcoal for the purification of H2O [3]. More recently, the British Empire added charcoal to water barrels to increase the durability of drinking water [4]. Nowadays, charcoal is used as animal feed because it helps in the health and growth of the animals [5]. Regarding clay minerals, the use of kaolinite or montmorillonite is actually employed in some medicine such as Kaopectate® due to its good antidiarrheal applications [2,6]. 8 (...)
Keywords: Biomedicina; Biomedical Applications; Mesoporous Materials